Brain transcriptome - Hitzemann, Robert; Mcweeney, Shannon (International review of neurobiology, 2014)
Published since 1959, International Review of Neurobiology is a well-known series appealing to neuroscientists, clinicians, psychologists, physiologists, and pharmacologists. Led by an internationally renowned editorial board, this important serial publishes both eclectic volumes made up of timely reviews and thematic volumes that focus on recent progress in a specific area of neurobiology research. This volume, concentrates on the brain transcriptome. Brings together cutting-edge research on the brain transcriptome.